The new Jim Crow: mass incarceration in the age of colorblindness - Alexander, Michelle (New Press, 2010)
"As the United States celebrates the nation's "triumph over race" with the election of Barack Obama, the majority of young black men in major American cities are locked behind bars or have been labeled felons for life. Although Jim Crow laws have been wiped off the books, an astounding percentage of the African American community remains trapped in a subordinate status - much like their grandparents before them." "In this incisive critique, former litigator-turned-legal-scholar Michelle Alexander provocatively argues that we have not ended racial caste in America: we have simply redesigned it. Alexander shows that, by targeting black men and decimating communities of color, the U.S. criminal justice system functions as a contemporary system of racial control, even as it formally adheres to the principle of color blindness. The New Jim Crow challenges the civil rights community - and all of us - to place mass incarceration at the forefront of a new movement for racial justice in America."--BOOK JACKET